Вплив розвивального навчання на розвиток ефективної пізнавальної діяльності та творчості особистості - Рябченко, Лілія Олександрівна (НТУ "ХПІ", 2012)
The article deals with the problem of developing training's influence on the creative personality's able to effective cognitive and professional activity formation. The central point of teacher's attention is the creation of personality-oriented situation due to each the creative human personality forms. The creativity - is the highest form of the motivation of behaviour.
Keywords: розвиток особистості; педагогічні теорії; концепція; типологія особистостей